The structure and phase composition of SiC epitaxial films, synthesized by atoms replacement - Bakranova, D.I.; Kukushkin, S.A.; Nussupov, K.Kh.; Osipov, A.V.; Beisenkhanov, N.B. (Recent Contributions to Physics, 2018)
In this paper, using X-ray diffraction, electron diffraction, atomic force microscopy and Raman microscopy the structure, phase composition and surface microstructure of SiC films, synthesized by substitution of atoms in a high-resistivity (111) oriented c-Si in a gas mixture of CO and SiH4 (264 Pa, 1250 ° C, 15 min) are studied. It is shown that 3C-SiC film is epitaxial and does not contain twins on the surface, the surface has a pyramidal structure with height variations up to 19 nm with a distinct fragmentation of grains with sizes of 100 to 200 nm. It is defined lateral dimensions of large crystals (85 × 110 µm) and average sizes of β-SiC nanocrystals (3 - 7 nm) with perfect structure in the transition region "film-substrate". An absence of large scratches on the SiC film surface is demonstrated. The developed crystalline surface of the film indicates the formation of high-quality SiC crystals due to the healing of contraction pores during a long time (15 min) high-temperature synthesis.
Keywords: thin films, silicon carbide, dilatation dipoles, structure, crystallization